El rechazo de Carl Menger a la economía matemática. Una aproximación - González, María Blanco González (REVISTA PROCESOS DE MERCADO, 2007)
This article tries, on the one hand, to analyse why Carl Menger, the Austrian School of Economics founder, rejected the use of mathematics as a tool for economic theory and the scope of his opposition. On the other hand, the article considers the advances in mathematical science in order to question at what point Menger’s methodology is still sounding, or on the contrary, if these new developments allow a wider use of mathematical economics maintaining, at the same time, the Austrian methodological assumptions. Nowadays, the Multicriteria Decision Theory has emerged as a powerful tool to assist in the process of searching for decisions, which best satisfy a multitude of conflicting objectives.These advancements may question the persistent opposition to mathematical economics not so much from Carl Menger but from his successors. Key words: Economic methodology, Austrian School of Economics, Carl Menger, mathematical economics, Multicriteria Decision Theory. JEL Classification: B1, B2, B4, C6, C8. Resumen: El objetivo de este documento de trabajo es, por un lado, analizar los motivos que llevaron al fundador de la Escuela Austriaca, Carl Menger, a rechazar el empleo de las matemáticas como herramienta de la teoría económica y el alcance de esta oposición. Por otra parte, se trata de considerar si actualmente esta postura metodológica sigue siendo válida o, por el contrario, los avances en la matemática permiten un empleo más amplio en la teoría económica manteniendo los postulados mengerianos. Hoy en día, la matemática también ha evolucionado y han aparecido disciplinas como la Teoría de la Decisión Multicriterio que intenta solucionar los problemas que afloran en la toma de decisiones cuando existen objetivos múltiples y, a menudo, conflictivos entre sí. Estos avances ponen sobre la mesa el recalcitrante rechazo hacia las matemáticas, no tanto de Menger, como de sus seguidores. Palabras clave: Metodología de la economía, Escuela Austriaca de Economía, Carl Menger, economía matemática, Teoría de la Decisión Multicriterio.